Role of Project Managers Skills in Supply Chain Management of Small Project's Marketing - Tamam Salman Khudhur; Hanan Safa Ali (International Journal of Supply Chain Management, 2019)
Abstract The research tackled the role of the project managers' skills in terms of its dimensions (intellectual, administrative, human and technical) and its impact on the supply chain management and marketing of small projects and the dimensions of the marketing mix, i.e., product/service, price, promotion and Place. The research problem focused on the nature of the relationship between the skills of project managers, The research also sought a set of objectives, the most important of which is the definition of the importance of small and medium enterprises and their role in reducing unemployment in the society if it is marketed appropriately and this is achieved through the enjoyment of leaders or project managers with skills to qualify for The questionnaire was distributed to the administrative staff and the 100 employees in different beauty centers in Baghdad. The research was based on the analytical descriptive method. The researcher used the answers of the questionnaire as an analytical tool in the practical side, based on the statistical program (spss) The research hypotheses reached a set of conclusions through testing and analysis of the hypotheses adopted by the research. The research concluded with a set of recommendations that could be taken by the managers of these projects.